Back to Basics : Economic Concepts Explained. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2017)
This paper discusses about capitalism that is often thought of as an economic system in which private actors own and control property in accord with their interests, and demand and supply freely set prices in markets in a way that can serve the best interests of society. The essential feature of capitalism is the motive to make a profit. In a capitalist economy, capital assets-such as factories, mines, and railroads-can be privately owned and controlled, labor is purchased for money wages, capital gains accrue to private owners, and prices allocate capital and labor between competing uses. Although some form of capitalism is the basis for nearly all economies today, for much of the past century it was but one of two major approaches to economic organization. In the other, socialism, the state owns the means of production, and state-owned enterprises seek to maximize social good rather than profits.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet